2017
DOI: 10.1039/c7cy01295k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the metal–support interaction in supported K-promoted NiMo catalysts for enhanced selectivity and productivity towards higher alcohols in CO hydrogenation

Abstract: Ni–KMoS/MMO catalysts were obtained using encapsulated Mo-based precursors to tune metal–support interaction, and enhanced selectivity and productivity towards higher alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Compared with bulk MoS 2 -based catalysts, supported Mo-based catalysts are desired to enhance activity and to improve higher alcohol selectivity using SiO 2 , CeO 2 , MgO, Al 2 O 3 , and carbon-based materials as supports. , Among those supports, mixed Mg/Al oxide (MMO) can tune the interaction between Mo and MMO to improve the product distribution toward higher alcohols. , The special nature of MMO of weakening the alcohols dehydration and favoring oxygenate coupling reactions may be helpful for the high selectivity of C 2 + alcohols . On the basis of the “Rim–Edge” model of MoS 2 catalysts, hydrogenation reactions only occurred on rim and edge sites. , It has also been reported that the high dispersion of MoS 2 on MMO with a proper layer number and slab size for more exposure of edge sites can enhance higher alcohol selectivity. ,, On the other hand, group VIII metals possess the potential for enhancing the activity and improving the HA selectivity by balancing the CO/H 2 activation and alcohols formation. Among these elements, Ni and Co are regarded as superior additives .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with bulk MoS 2 -based catalysts, supported Mo-based catalysts are desired to enhance activity and to improve higher alcohol selectivity using SiO 2 , CeO 2 , MgO, Al 2 O 3 , and carbon-based materials as supports. , Among those supports, mixed Mg/Al oxide (MMO) can tune the interaction between Mo and MMO to improve the product distribution toward higher alcohols. , The special nature of MMO of weakening the alcohols dehydration and favoring oxygenate coupling reactions may be helpful for the high selectivity of C 2 + alcohols . On the basis of the “Rim–Edge” model of MoS 2 catalysts, hydrogenation reactions only occurred on rim and edge sites. , It has also been reported that the high dispersion of MoS 2 on MMO with a proper layer number and slab size for more exposure of edge sites can enhance higher alcohol selectivity. ,, On the other hand, group VIII metals possess the potential for enhancing the activity and improving the HA selectivity by balancing the CO/H 2 activation and alcohols formation. Among these elements, Ni and Co are regarded as superior additives .…”
Section: Introductionmentioning
confidence: 99%
“…H 2 -TPR was carried out to examine the effects of Zn on the reducibility of K,NiMo/Zn 0.7 Al 0.3 , K,NiMo/Zn 0.35 Mg 0.35 Al 0.3 , and K,NiMo/Mg 0.7 Al 0.3 . Figure b and Table present two main peaks on three oxidic catalysts where the peak at low temperature can be ascribed to the reduction from Mo 6+ to Mo 4+ of octahedral molybdenum (Mo­(o)) oxide, and the peak located at high temperature can be assigned to the deep reduction of Mo species in tetrahedral sites (Mo­(t)) or the reduction of Mo 4+ to metallic Mo. ,, It is difficult to assign Ni reduction temperatures because the reduction peak of Ni may overlapped with Mo signals. , The TPR of K,Mo/Zn 0.7 Al 0.3 was also performed to investigate the overlap of the reduction of Ni and Mo species (Figure S2). The results suggest that the addition of Ni can promote the reduction of Mo species .…”
Section: Results and Discussionmentioning
confidence: 99%
“…14,15 It is worth noting that Zn can also be used to tune the acidity/alkalinity by partially neutralizing inherent strong acidic sites. 16−19 Our previous work 3,4,20 showed that the integration of surfactant-encapsulated molybdenum precursors and hydrothermal methods can modulate the interaction between molybdenum species and supports, successfully increasing the selectivity of C 2+ OH and the total alcohol yield. The HAS performance is greatly influenced by acidic/alkaline and structural properties.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations